Hygiene Behavior of Adolescent Girls at SMKN 1 Bengkulu City - Nur Eriska; Deni Maryani; Novianati Novianati; Sri Nengsi Destriani; Dara Himalaya (Universitas Ibn Khaldun Bogor, 2026)
Menstruation is a physiological process experienced by adolescent girls as a sign of the functioning of reproductive organs. During menstruation, adolescent girls need to maintain reproductive hygiene to prevent health problems such as infection and vaginal discharge. One factor that influences hygiene behavior is the level of knowledge about menstruation. Objective: This study aims to determine the relationship between the level of knowledge about menstruation and reproductive hygiene behavior in adolescent girls at SMKN 1 Bengkulu City. This study used a quantitative method with a cross-sectional design. The population in this study were all 508 female students in grades X and XI of SMKN 1 Bengkulu City. The research sample of 84 respondents was determined using the Slovin formula with a simple random sampling technique. Data were collected using a questionnaire on menstrual knowledge and reproductive hygiene behavior that had been tested for validity and reliability. Data analysis was carried out univariately and bivariately using the chi-square test. The results showed that most respondents had a good level of menstrual knowledge (51 respondents (60.7%) and good reproductive hygiene behavior (41 respondents (48.8%). The chi-square test results obtained a p value of 0.000 (p < 0.05), indicating a significant relationship between the level of menstrual knowledge and reproductive hygiene behavior during menstruation in adolescent girls at SMKN 1 Bengkulu City. There is a significant relationship between the level of menstrual knowledge and reproductive hygiene behavior in adolescent girls. Therefore, it is necessary to improve reproductive health education in schools to increase knowledge and develop better hygiene behavior during menstruation.